Gate-sharing and talent distribution in the English football league - Terry Robinson; Robert Simmons (The University of Manchester, Manchester Business School, 2009)
Using a data base of the movements of over two thousand professional footballers in the top two divisions of the English Football League between 1969 and 1995, this article examines the impact on talent distribution through the movement of players after gate-revenue sharing was abandoned in this league in 1983 and compares the results with the predictions of the Walrasian and Nash theoretical models presented by Rottenberg (1956), Quirk and Fort (1992), Vrooman (1995), and Szymanski and Kesenne (2004). It is found that there is an increased probability that players would move from teams in the second tier of the league to teams in the first tier after gate-sharing was abolished. We also find that there is increased probability that players will be transferred within divisions. These results go against one of the main theoretical predictions of the sports economics literature - that gate sharing will have no effect on competitive balance.
Keywords: 330; Fußballsport; Professioneller Sport; Personalbeschaffung; Wettbewerbsstrategie; Sportverband; Großbritannien